Muslim-Friendly Hotel in Malaysia: The Development, Operating Concept and Associated Issues - Hashim, Nur Iman; Mohd Fauzi, Nadzirah (Online Journal of Research in Islamic Studies, 2022)
Over the last decade, there has been a growing emphasis on the creation of Islamic-related products and services. In response to this trend, hotels developed novel offerings for Muslim customers known as Muslim-Friendly Hotels. However, there has been a paucity of study on the features and implementation of Muslim-Friendly Hotels in the hotel business. As a result, the goal of this study is to better understand the practise of Muslim-Friendly Hotels in Malaysia. A focus group discussion was conducted in this preliminary study to get a knowledge of the practise and issues connected with using the MFH concept in hotel operations in Malaysia. In total, six panels were part in the discussion. The debate was recorded, and the dialogue, as well as the remarks made throughout the discussion, were transcribed, and then categorised based on the questions raised during the discussion. In general, this research discovered three issues in implementing Muslim-Friendly Hotels in Malaysia, including the uncertainty of government regulation, the lengthy procedure of obtaining the Halal certificate, and the lack of a solid supporting system to support the implementation of Muslim-Friendly Hotels. In addition, two Malaysian Standards, MS1900:2005 and MS2610:2015, have been recognised and strongly recommended for incorporation as a unified system in implementing the Muslim-Friendly Hotel idea.